Barriers to staff adoption of a surgical safety checklist. Issue 3 (7th November 2011) - Fourcade, Aude; Blache, Jean-Louis; Grenier, Catherine; Bourgain, Jean-Louis; Minvielle, Etienne
Abstract : Objective: Implementation of a surgical checklist depends on many organisational factors and on socio-cultural patterns. The objective of this study was to identify barriers to effective implementation of a surgical checklist and to develop a best use strategy. Setting: 18 cancer centres in France. Design: The authors first assessed use compliance and completeness rates of the surgical checklist on a random sample of 80 surgical procedures performed under general or loco-regional anaesthesia in each of the 18 centres. They then developed a typology of the organisational and cultural barriers to effective checklist implementation and defined each barrier's contents using data from collective and semi-structured individual interviews of key staff, the results of an email questionnaire sent to the 18 centres, and direct observations over 20 h in two centres. Results: The study consisted of 1440 surgical procedures, 1299 checklists, and 28 578 items. The mean compliance rate was 90.2% (0, 100). The mean completion rate was 61% (0, 84). 11 barriers to effective checklist implementation were identified. Their incidence varied widely across centres. The main barriers were duplication of items within existing checklists (16/18 centres), poor communication between surgeon and anaesthetist (10/18), time spent completing the checklist for no perceived benefit, and lack of understanding and timing of item checks (9/18), ambiguity (8/18), unaccounted risks (7/18) and a time-honoured hierarchy (6/18). Conclusions: Several of the barriers to the successful implementation of the surgical checklist depended on organisational and cultural factors within each centre. The authors propose a strategy for change for checklist design, use and assessment, which could be used to construct a feedback loop for local team organisation and national initiatives.